Outcomes of Antituberculous Therapy in Patients Undergoing Decortication for Tuberculous Empyema and Its Association with Duration of Antituberculous Therapy - Zahid, Muhammad Toqeer; Farooq, Muhammad Nabeel; Khan, Ali Raza (Biological and Clinical Sciences Research Journal, 2025)
Empyema is a severe pleural complication of tuberculosis that often requires surgical decortication when organized pleural disease leads to trapped lung and impaired respiratory mechanics. Although antituberculous therapy (ATT) is the cornerstone of treatment, the optimal duration of preoperative ATT before decortication remains uncertain, particularly in high-burden countries such as Pakistan. This study evaluated postoperative outcomes of decortication in relation to the duration of preoperative ATT. Objective: To determine the outcomes of antituberculous therapy in patients undergoing decortication for tuberculous empyema and to assess the association between postoperative outcomes and the duration of preoperative ATT. Methods: This descriptive case series was conducted in the Department of Thoracic Surgery, Gulab Devi Teaching Hospital, Lahore, from 19 December 2024 to 19 June 2025. A total of 80 adult patients with tuberculous empyema undergoing decortication were enrolled through consecutive non-probability sampling. Patients were divided into two equal groups based on the duration of preoperative ATT: Group A received ATT for more than 6 weeks, while Group B received ATT for less than 6 weeks. Outcomes assessed on the seventh postoperative day included air leak, mechanical ventilator requirement, intensive care unit (ICU) admission, and residual pleural collection. Data were analyzed using SPSS version 29, with p≤0.05 considered statistically significant. Results: The mean age of the patients was 39.8±13.4 years, and 65.0% were male. Postoperative complications were significantly more frequent in patients receiving ATT for less than 6 weeks. Air leak occurred in 17.5% of Group A versus 40.0% of Group B (p=0.026), mechanical ventilator requirement in 7.5% versus 25.0% (p=0.032), ICU admission in 10.0% versus 30.0% (p=0.024), and residual collection in 12.5% versus 35.0% (p=0.018). Overall, at least one complication was recorded in 47.5% of Group A compared with 77.5% of Group B (p=0.006). Conclusion: A preoperative ATT duration of more than 6 weeks was associated with significantly better early postoperative outcomes after decortication for tuberculous empyema. Optimizing ATT duration before surgery may reduce postoperative morbidity and improve recovery in patients with tuberculous empyema.